1993
DOI: 10.1002/jnr.490350213
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary fish oil enriches docosahexaenoate levels in brain subcellular fractions of offspring

Abstract: Prompted by the speculated essentiality of docosahexaenoic acid (DHA) for neural development, this study was undertaken to investigate the incorporation of (n-3) fatty acids in the maternal diet into various phospholipids of infant rat brain subcellular fractions: microsomes (Ms), synaptosomes (Sy), myelin (My), and mitochondria (Mt). Two groups of infant rats were nourished by dams fed diets containing 20% of either corn oil (CO) or menhaden oil (MO) from 2 until 12 days of age. DHA but not eicosapentaenoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Significantly, potentially ketogenic polyunsaturated fatty acids (PUFAs) such as linoleic, arachidonic and docosahexaenoic acids [15] exhibit facile transfer across the blood-brain barrier during the suckling period [16,17]. Furthermore recent hybridization studies in situ [18,19] have demonstrated the localization of the peroxisome proliferator-activated receptor α (PPARα), a nuclear transcription factor that is activated by a variety of PUFA ligands [20,21], to certain brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, potentially ketogenic polyunsaturated fatty acids (PUFAs) such as linoleic, arachidonic and docosahexaenoic acids [15] exhibit facile transfer across the blood-brain barrier during the suckling period [16,17]. Furthermore recent hybridization studies in situ [18,19] have demonstrated the localization of the peroxisome proliferator-activated receptor α (PPARα), a nuclear transcription factor that is activated by a variety of PUFA ligands [20,21], to certain brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipid fatty acid analyses were conducted according to the methods of Yeh et al [1993]. Briefly, myelin fractions from hindbrain homogenates were resuspended in 1.2 ml of deionized water and added to 20 ml of chloroform:methanol (2:1, v/v) for lipid extraction with butylated hydroxytoluene as the antioxidant.…”
Section: Lipid Extraction and Analysesmentioning
confidence: 99%
“…The gas chromatographic conditions were the same as those described elsewhere (38). For fatty acid analysis of phospholipid species, the lipid extracts were separated into phosphatidylcholine (PC) and phosphatidylethanolamine (PE) by thin-layer chromatography using silica G plates and a solvent mixture of chloro-form/methanol/petroleum ether (bp 35-60°C)/acetic acid /boric acid (40:20:30:10:1.8; vol/vol/vol/vol/wt) as described in a previous study (39). The isolated individual phospholipids were transmethylated and analyzed by gas chromatography (38).…”
Section: Methodsmentioning
confidence: 99%